A Multi-step High-Performance Liquid Chromatography (HPLC) Technique for the Extraction and Purification of Medical-Grade Cyclosporine A - Issaka, Eliasu; Amu-Darko, Jesse Nii Okai; Adams, Mabruk; Aguree, Sylvenus; Enyan, Michael; Sulemana, Husseini; Suleimana, Princess Firdaus (Fine Chemical Engineering, 2024)
Cyclosporine A (CsA), a potent immunosuppressive drug, is used to treat autoimmune diseases and prevent organ transplant recipients from rejecting their new organs. Maintaining CsA’s uniformity and purity is essential to maintaining its therapeutic efficacy and safety. Impurities and contaminants in CsA formulations can exacerbate side effects and patient toxicity. Purification processes can improve the safety profile of the drug and reduce the likelihood of adverse effects by eliminating impurities. Using High-performance liquid chromatography (HPLC) methods, CsA has been isolated and refined from crude in recent years. However, after the procedure, the CsA purity was not at its best. To solve this issue, this work employs a multi-step HPLC method to increase purity levels to above 95%. When exploring the HPLC detection conditions of CsA, we found that the method from the Chinese pharmacopoeia: acetonitrile-water-tert-butyl methyl ether-phosphoric acid (430 : 520 : 50 : 1) was a better mobile phase solution, our further research, including the substitution of tert-butyl methyl ether with other buffer solvents, showed no significant improvement. At the same time, we established that the key factor affecting its separation was temperature. When the temperature is lower than 70 ℃, the HPLC separation effect worsens, the retention time increases, and the peak width becomes longer. Finally, the utilization of acetonitrile-water-tert-butyl methyl ether-phosphoric acid (430 : 520 : 50 : 1) as the mobile phase with a column temperature of 70 °C, petroleum ether: acetic acid Ethyl ester (70 : 30) as the mobile phase, and filling the φ 40 mm × 500 mm chromatography column using a 40 60 μm silica gel so that a 10 : 1 height-to-diameter ratio of the packed part is obtained, under normal temperature conditions, resulted in an average cyclosporine A yield of 80.1%. The corresponding average purity was 97.2%, of which the first isolation yield was 82.3%, and the purity was 98.1%.